The Impact of Obesity in the UAE: Real-world Physician and Patient Perspectives - Rita Nawar; Rahila Bhatti; Fatih Tangi; Soniya Rai; Tatjana Isailovic; Swarna Khare; Esther Artime; Victoria Higgins; Andrea Leith; Fatheya Al Awadi (Dubai Diabetes and Endocrinology Journal)
Background: Limited evidence exists on the impacts of obesity in the United Arab Emirates (UAE). Real-world evidence is required to support obesity-related healthcare decision-making in the UAE.